2019
DOI: 10.1186/s12885-019-5504-9
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume/platelet count ratio in colorectal cancer: a retrospective clinical study

Abstract: Background Mean platelet volume (MPV) is a marker of platelet activation. MPV and platelet count (PC) are negatively correlated, and their ratio (MPV/PC) is informative for the diagnosis of malignant tumors. However, the relationship between MPV/PC and colorectal cancer is unclear. This retrospective clinical study aimed to evaluate the diagnostic value of MPV/PC in colorectal cancer. Methods Hematological examinations were performed at initial diagnosis in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 35 publications
6
52
1
Order By: Relevance
“…Many studies have shown that thrombocytosis plays a role in cancer genesis and development [10,11]. Increasing evidence has indicated that platelet count correlates with prognosis in various malignancies, such as lung, renal, gastric, colorectal and hepatocellular cancer and is considered a hallmark of cancer [12][13][14][15][16]. Additionally, the platelet count is convenient to perform, less expensive, and easily available.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that thrombocytosis plays a role in cancer genesis and development [10,11]. Increasing evidence has indicated that platelet count correlates with prognosis in various malignancies, such as lung, renal, gastric, colorectal and hepatocellular cancer and is considered a hallmark of cancer [12][13][14][15][16]. Additionally, the platelet count is convenient to perform, less expensive, and easily available.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has indicated that platelet count correlates with prognosis in various malignancies, such as lung, renal, gastric, colorectal and hepatocellular cancer and is considered a hallmark of cancer [12][13][14][15][16] . Additionally, the platelet count is convenient to perform, less expensive, and easily available.…”
Section: Introductionmentioning
confidence: 99%
“…P-LCR is the percentage of PLTs with a size of more than 12 fL (Fig 1). The PLT count has been shown to be an important severity index in several diseases, such as malaria [5], colorectal cancer [6] and acute kidney injury [7]. It is noteworthy that the PLT count is also a convenient marker of liver fibrosis in several hepatic diseases, such as nonalcoholic fatty liver disease [8], hepatitis B [9] and C [10].…”
Section: Introductionmentioning
confidence: 99%